RELATIONSHIP BETWEEN LEVEL OF EDUCATION ANDEMPLOYEES OF PARENTS WITH CHILDREN AT HOME ON THE CHARACTEROF PEOPLE PARTICIPANTS - Halimatussakdiah Halimatussakdiah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThis study aims to determine the relationship level of education and intimacy of parents with children at home to the character of students in class IV SDN 106811 Bandar Setia. This research belongs to correlational research using quantitative descriptive method. The sample in this research is the students of class IVA and IVB SD Negeri 106811 Bandar Setia which amounted to 64 people. Based on the results of research and hypothesis testing showed that: There is no positive and significant relationship between the level of education of parents to the character of learners; There is a positive and significant relationship between the parent's familiarity with the child at home to the character of the students; And There is a positive and significant relationship between the level of parent education and the familiarity of parents with children at home to the character of learners.Keywords:Character, Education Level, Parent's Familiarity withChildren